(untitled)
We study the effect of international trade and freeness of trade on interregional inequality within countries. We estimate a model derived from a structural economic geography approach where interregional inequality depends on weighted trade shares and trade costs and where we can derive an aggregate freeness of trade measure. These measures are instrumented based on constructed trade shares and trade costs tted from a gravity model of bilateral trade, which covers 208 countries for the period 19482006. We analyze a cross country data set of regional inequality within countries, which covers 110 countries (1569 sub-national regions) for the year 2005, and a panel data set, which covers 56 countries (835 sub-national regions) for the period 19802009. IV and dynamic panel regressions show that trade increases inter-regional inequality within countries but an increase in freeness of trade is probably neutral. Because the latter is an indicator for integration in the world markets, we conclude that more integration neutralizes the negative interregional distribution e ects of the increase in trade., address = Kiel und Hamburg, author = Georg Hirte and Christian Leßmann, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, keywords = F15; R10; R12; 330, language = eng, number = D18-V3, publisher = ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, series = Beiträge zur Jahrestagung des Vereins für Socialpolitik 2014: Evidenzbasierte Wirtschaftspolitik - Session: International Trade and Development, title = Trade, Integration and Interregional Inequality, url = https://hdl.handle.net/10419/100610, year = 2014